The Effect of Entrepreneurship Education and Adversity Quotient on Entrepreneurial Intentions Mediated by Entrepreneurial Attitudes on State Vocational High School Students in East Jakarta - Safira, Nabela; Saptono, Ari; Pratama, Aditya (The Future of Education Journal, 2025)
This study aims to determine the effect of entrepreneurship education and adversity quotient on entrepreneurial intentions through entrepreneurial attitudes. The research was conducted on state vocational high school students in East Jakarta through a survey method using a research instrument by questionnaire. The affordable population used in the study is 11th-grade students of State Vocational High School 40 and 46 Jakarta as many as 502 students with a proportionate stratified random sampling technique, which obtained a sample of 223 students. The data used in the study is quantitative data with analysis through SEM-PLS. The results showed that: (1) There is a direct effect of entrepreneurship education on entrepreneurial intention; (2) There is no direct effect of adversity quotient on entrepreneurial intention; (3) There is a direct effect of entrepreneurship education on adversity quotient; (4) There is a direct effect of entrepreneurship education on entrepreneurial attitude; (5) There is a direct effect of adversity quotient on entrepreneurial attitude; (6) There is a direct effect of entrepreneurial attitude on entrepreneurial intention; (7) Entrepreneurship education has an indirect effect on entrepreneurial intention through entrepreneurial attitude; (8) Adversity quotient has an indirect effect on entrepreneurial intention through entrepreneurial attitude. The coefficient of determination in this study amounted to 48.5% which shows the ability of entrepreneurship education, adversity quotient and entrepreneurial attitudes in influencing entrepreneurial intention while the remaining is influenced by other variables outside the study.